Metformin directly suppresses atherosclerosis in normoglycaemic mice via haematopoietic adenosine monophosphate-activated protein kinase - Seneviratne, Anusha (Cardiovasc Res, 2020)
AIMS: Atherosclerotic vascular disease has an inflammatory pathogenesis. Heme from intraplaque haemorrhage may drive a protective and pro-resolving macrophage M2-like phenotype, Mhem, via AMPK and activating transcription factor 1 (ATF1). The antidiabetic drug metformin may also activate AMPK-dependent signalling. Hypothesis: Metformin systematically induces atheroprotective genes in macrophages via AMPK and ATF1, thereby suppresses atherogenesis. METHODS AND RESULTS: Normoglycaemic Ldlr(−/−) hyperlipidaemic mice were treated with oral metformin, which profoundly suppressed atherosclerotic lesion development (P < 5 × 10(−11)). Bone marrow transplantation from AMPK-deficient mice demonstrated that metformin-related atheroprotection required haematopoietic AMPK [analysis of variance (ANOVA), P < 0.03]. Metformin at a clinically relevant concentration (10 μM) evoked AMPK-dependent and ATF1-dependent increases in Hmox1, Nr1h2 (Lxrb), Abca1, Apoe, Igf1, and Pdgf, increases in several M2-markers and decreases in Nos2, in murine bone marrow macrophages. Similar effects were seen in human blood-derived macrophages, in which metformin-induced protective genes and M2-like genes, suppressible by si-ATF1-mediated knockdown. Microarray analysis comparing metformin with heme in human macrophages indicated that the transcriptomic effects of metformin were related to those of heme, but not identical. Metformin-induced lesional macrophage expression of p-AMPK, p-ATF1, and downstream M2-like protective effects. CONCLUSION: Metformin activates a conserved AMPK-ATF1-M2-like pathway in mouse and human macrophages, and results in highly suppressed atherogenesis in hyperlipidaemic mice via haematopoietic AMPK.